Phytochemical Screening and In-vitro Evaluation of Antioxidant Activity and Antimicrobial Activity of the Leaves of Sesbania sesban (L) Merr. - RP, Mani; Awanish, Pandey; Shambaditya, Goswami; Poonam, Tripathi; V, Kumudhavalli; Pratap, Singh Ajay (Free Radicals and Antioxidants)
Introduction: Antioxidants are micronutrients that have gained importance in recent years due to their ability to neutralize free radicals or their actions. Sesbania sesban (L) Merr is an ancient plant which is traditionally used as an antioxidant folklore plant. The present research deals with the phytochemical screening and in vitro evaluation of antioxidant activity of the leaves of Sesbania sesban (L) Merr. Methods: The ethanolic extract of the plant Sesbania sesban (L) Merr was subjected for the phytochemical screening. The preliminary screening reports the presence of Saponin, Tanin, Phenolic compound, Flavonoid in ethanolic extracts. DPPH scavenging activity or the Hydrogen donating capacity was quantified in presence of stable DPPH radical on the basis of Blois method. NO scavenging activity was performed in the presence of nitric oxide was generated from sodium nitroprusside and measured by the Greiss reaction according to the method of Marcocci. Ascorbic acid was used as standard for the both. Results: The scavenging was found to dose dependent. Thus extract has been established the as an antioxidant. The reducing capacity serves as significant indicator of antioxidant activity. The reducing power increased with the increasing concentration of sample. Conclusion: The folklore use of Sesbania sesban (L)Merr has been proved in present research work. Further studies along with isolation and molecular mechanism on extract of Sesbania sesban (L) Merr may lead to significant out come.
Keywords: Sesbania sesban (L) Merr; DPPH scavenging activity; NO scavenging activity; Ascorbic acid; Phytochemical screening